Pengaruh Perceived Usefulness, Perceived Ease of Use, dan Compatibility with Lifestyle terhadap Intention to Use Fitur Social Commerce - Dyan Erlyn Oktania; Tias Andarini Indarwati (Nomicpedia: Journal of Economics and Business Innovation, 2022)
Social media companies began to grow their business by making innovations in shopping features. The intention to use shopping features is influenced by several factors, including perceived usefulness, perceived ease of use, and compatibility with lifestyle. The purpose of this study was to find out the influence of perceived usefulness, perceived ease of use, and compatibility with lifestyle on the intention to use features of TikTok Shop. This type of research is quantitative research with judgemental sampling methods. An online questionnaire with a Likert scale of 1-5 was distributed to 100 respondents via social media TikTok. Data analysis techniques use multiple linear regression tests with the help of IBM SPSS 20. The results showed that perceived usefulness, perceived ease of use, and compatibility with lifestyle had a significant and positive effect on the intention to use. Based on the result, it is recommended that TikTok can develop creative marketing strategies by paying attention to the usability, ease, and compatibility of the TikTok Shop features with the user's lifestyle in order to increase the intention to use.